Evaluation of clinical parameters related to methotrexate therapy in lichen planus - Hazra, Samaresh Chandra; Choudhury, Agha Masood; Khondker, Lubna; Khan, Md. Shirajul Islam; Rashid, Muhammad Munir (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: For better management of lichen planus a clinical trial of oral methotrexate is necessary in ow· country. Objective: The objective of this study is to evaluate efficacy and safety ofmethotrexate therapy in the treatment of lichen planus. Methods: It was a prospective randomized controlled clinical trial conducted in the department of Dermatology and Venereology, BSMMU, Dhaka, from January 2009 to December 2010. Forty four patients of lichen planus were included in the study. Cases (group-A, n=23) were treated with methotrexate (10 mg) single morning dose and control (group-B, n=21) were treated with mini pulse betamethasone (5mg) single morning dose on 2 consecutive days during the period of 12 weeks. Results: Clinical parameters were measured by follow up clinical examination. Morphological lesion of lichen planus improved 95. 7% in group-A and only 28.6% improved in group-B. At the end of study 82.6% bad no complaints of itching in group-A and 100% had no complaints of itching in group-B. 16(69.6%) patients in group-A were completely cured clinically but 10(47.6%) in group-B. Anemia 3(14.2%) and edema 12(57.1 %) developed in group-B but none in group-A. In group-B, dyspepsia 15(71.4%), acne 10(47.6%),mooning face 8(38.1%), striae 8(38.1%) and hypertrichosis 4(19.0%) developed but none in group-A lntermittenr diarrhoea, headache, nausea and fatigue complained in both groups of patients but the percentage of complaints was higher amog group-8 compared to group-A. Menstrual abnormality developed in group-B 5(71.4%) but none in group-A. Conclusion: The overall adverse effects were less in group-A than group-B. Therefore, methotrexate can be used as an alternative safer option for the treatment of lichen planus.